Characteristics of Injuries in Road Traffic Accident Victims: An Autopsy Study at Srinagarind Hospital, Khon Kaen University, Thailand - Narin Chutrakoon; Wirut Khunkitti; Wunchana Seubwai; Thitichai Wiangsimma (Siriraj Medical Journal, 2025)
Objective: This ambidirectional cohort study aimed to investigate injury characteristics in road traffic accident (RTA) victims based on autopsy cases at the Department of Forensic Medicine, Srinagarind Hospital, Faculty of Medicine, Khon Kaen University, Thailand.